Career counselors' attitudes about employment-related skills of individuals with autism spectrum disorders in Greece - Stampoltzis, Aglaia; Peristeri, Eleni; Kalouri, Rany (Frontiers in Education, 2025)
BackgroundIndividuals with Autism Spectrum Disorder (ASD) possess a unique range of strengths and challenges that can impact their employment opportunities and their vocational outcomes. Career counselors' role in helping individuals with ASD to their transition to employment has not been fully understood.ObjectiveThe aim of the current study was threefold: (a) to explore career counselors' views and attitudes toward employability skills in transition aged individuals with ASD in Greece; (b) to investigate the counselors' perception of the challenges they face when working with this population; and (c) to highlight career counselors' judgment of the suitability of professions for autistic individuals. For the first and second aim, we used an exploratory and confirmatory factor analysis.MethodsAn original 28-item survey was developed and disseminated to career counselors. A total of 92 professionals (62 women) took part in the study. All of them have been working as career counselors in the public or private sector. The factor structure of the survey's items was examined using quantitative data analysis, namely, an exploratory and confirmatory factor analyses factor method.ResultsAccording to the results of the exploratory and confirmatory factor analysis, as well as descriptive statistics, we found that counselors agreed that social competence and high self-esteem can promote positive professional development in people with ASD, and that technology can have positive effects in their career. Over half of the counselors surveyed think there are professions particularly well-suited to individuals with ASD and they expressed a strong desire for ASD-specific training to be better prepared to meet the needs of their clients.ConclusionThe results of the study represent the first step toward key variables in vocational guidance for individuals with ASD in Greece that can guide future research.